High temperature resistant rapid cooling high performance concrete and preparation method thereof

By introducing temperature gradient composite aggregate and other high-performance materials into the concrete, the multi-layer structural design and materials synergistically work, the problem of large temperature gradient and reduced strength of concrete under high temperature and rapid water-cooling coupling conditions is solved, and the effect of concrete maintaining good performance after fire is achieved.

CN118930170BActive Publication Date: 2025-03-11JIANGSU CHINA CONSTR COMMERCIAL CONCRETE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410992510.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-23
Publication Date
2025-03-11
Estimated Expiration
2044-07-23

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the internal and external temperature gradient of concrete under high temperature and rapid water-cooling coupling conditions, resulting in a decrease in structural strength and durability.

Method used

Temperature gradient composite aggregate, silicon carbide, fiber and other materials are introduced into concrete. Through the multi-layer structure design and the synergistic effect of materials, the temperature gradient of concrete under high-temperature quench conditions is reduced, and crack resistance and compactness are improved.

Benefits of technology

It effectively reduces the temperature gradient of concrete under high-temperature quenching conditions, reduces cracking and strength reduction problems caused by temperature stress, improves the comprehensive performance of concrete, and extends the service life of the building.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention discloses a high-temperature resistant rapid cooling high-performance concrete and a preparation method thereof, and belongs to the technical field of building materials. The raw materials of the concrete include by weight: 240-300 parts of cement, 60-80 parts of fly ash, 60-70 parts of granulated blast furnace slag, 700-780 parts of sand, 0.8-1.3 parts of round-shell psyllium husk glue, 1.5-2.5 parts of basalt fiber, 5-8 parts of water reducer, 155-170 parts of water, 1020-1100 parts of temperature gradient composite aggregate, 8-10 parts of silicon carbide, and 0.5-1.5 parts of polyethylene glycol. The present invention introduces materials such as temperature gradient composite aggregate, silicon carbide, and round-shell psyllium husk glue into concrete, so that the internal and external temperature gradients of concrete are greatly reduced under high-temperature rapid cooling conditions, and the density and crack resistance can still be maintained at a high level, which can effectively solve the problems of cracking and accelerated strength reduction caused by large temperature stress in concrete, and extend the service life of engineering structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to high-temperature resistant rapid cooling high-performance concrete and a preparation method thereof. Background Art

[0002] In recent years, fires in concrete structures have occurred frequently, especially in densely populated urban buildings. Once a fire occurs, it will cause huge losses of life and property. During a fire, heat is input into the structure through thermal radiation, thermal convection and heat conduction. The structural thermal coupling effect causes significant changes in the microstructure of the concrete, which directly leads to a significant decrease in its mechanical and durability properties. In reality, the fire department usually rescues the building in time after the fire occurs, and generally uses water spray cooling to extinguish the fire and quickly cool down the concrete structure. Therefore, compared with the natural cooling of other civil engineering structures after being subjected to high temperature conditions, rapid cooling is more in line with the actual working conditions of urban buildings after a fire.

[0003] Compared with the single high temperature condition and the natural cooling condition after high temperature, the rapid cooling condition after high temperature by water spraying is more severe, and the main hazards to concrete include the following two aspects: (1) large temperature gradient and high thermal stress: after the concrete experiences high temperature, the internal temperature rises sharply and the material expands. At this time, it encounters water spray cooling, and the external temperature drops rapidly, causing the concrete surface to shrink, while the interior remains high temperature. A large temperature gradient is generated between the two, which causes large temperature stress, directly leading to cracks on the surface and inside of the concrete and damage to the overall structure; (2) accelerated reduction of material strength: high temperature accelerates the decomposition of hydration products and gel in concrete, increases porosity, and makes the structure loose. The microscopic cracks and spalling phenomena generated during the rapid cooling process of water spraying will further aggravate this process, resulting in a significant reduction in material strength. Therefore, how to reduce the internal and external temperature gradient of concrete while improving strength and crack resistance is the key to reducing the performance degradation of engineering structures under the coupled conditions of high temperature and rapid water cooling.

[0004] In the prior art, most of the designs are only for the high temperature resistance of concrete, and few consider the application conditions of concrete under the coupling effect of high temperature and rapid cooling by water spraying, and there is no solution to the further damage caused by rapid water cooling of concrete at high temperature. For example, Chinese patents CN 117886568 A and CN 115124291A both disclose a high temperature resistant concrete and its preparation method: Patent CN 117886568A uses refractory materials such as magnesium slag, forsterite whiskers, and wollastonite fibers to achieve concrete without cracks and structural damage at 1000°C and below; Patent CN 115124291A uses solid waste fireproof materials such as steel slag, ferrochrome slag, and microsilica powder, combined with fibers and titanium carbide silicon powder, so that the prepared concrete has high compressive strength and flexural strength at room temperature, and stable high temperature resistance. The common feature of these two patented technologies is that they improve the strength and high-temperature performance of concrete by adding a variety of fireproof materials, without considering the technical problems that concrete under coupled working conditions may encounter, such as large internal and external temperature gradients and high thermal stress. In addition, the superimposed design of multiple fireproof materials is not easy to obtain at the same time during the actual production of concrete mixing plants, and there are problems with the precise amount of addition and mixing uniformity, which will inevitably affect the working performance of concrete. Chinese patent CN 117819909 A uses porous mesh lightweight aggregate and modified carbon fiber to prepare high-temperature resistant high-strength concrete, but the surface of the porous mesh lightweight aggregate is rough, which can easily affect the pumpability of concrete construction, and the porous structure of the aggregate can easily lead to uneven infiltration of the slurry, and the aggregate-cement slurry interface transition zone is weak, which reduces the mechanical properties of the concrete.

[0005] Therefore, it is of great significance to extend the service life of buildings to study how to effectively reduce the impact of large temperature gradients, shrinkage cracking and structural looseness on the structural strength and durability of concrete under high temperature and rapid water cooling coupling conditions, so that the concrete structure can still retain good comprehensive performance after experiencing fire and water spraying. Summary of the invention

[0006] In view of the deficiencies of the above prior art, the purpose of the present invention is to provide a high-temperature resistant rapid cooling high-performance concrete and a preparation method thereof. By introducing temperature gradient composite aggregate, silicon carbide, fiber and other materials into concrete, the internal and external temperature gradients of the concrete are greatly reduced under high-temperature rapid cooling conditions, and the concrete still maintains excellent crack resistance and density, effectively solving the problems of cracking and accelerated strength reduction of concrete due to large temperature stress.

[0007] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0008] A high-temperature resistant rapid cooling high-performance concrete, the raw materials of which include, by weight: 240-300 parts of cement, 60-80 parts of fly ash, 60-70 parts of granulated blast furnace slag, 700-780 parts of sand, 0.8-1.3 parts of psyllium husk glue, 1.5-2.5 parts of basalt fiber, 5-8 parts of water reducer, 155-170 parts of water, 1020-1100 parts of temperature gradient composite aggregate, 8-10 parts of silicon carbide, and 0.5-1.5 parts of polyethylene glycol; wherein the preparation method of the temperature gradient composite aggregate includes the following steps:

[0009] (1) Preparation of inner layer matrix: 65-75 parts of coal gangue, 15-20 parts of expanded perlite powder, 8-10 parts of hollow glass microspheres and 3-5 parts of sodium silicate solution were mixed evenly, allowed to stand for 16-20 hours, granulated and sintered to obtain particles with a particle size of 4.75-16.0 mm.

[0010] (2) Preparing an intermediate heat-absorbing buffer layer: mixing the particles obtained in step (1) with polyethylene wax heated to a molten state, vacuum impregnating, and then adding industrial waste glass powder. After mechanical shaking and mixing evenly, the mixture is taken out and allowed to stand and dry to obtain composite particles with a particle size of 5 to 20 mm. The weight ratio of the particles obtained in step (1), polyethylene wax, and industrial waste glass powder is 1: (0.3 to 0.4): (0.4 to 0.5).

[0011] (3) Preparation of external thermal conductive and strength coating layer: Mix 65-75 parts of aluminum sludge ash, 15-25 parts of slag powder, and 8-12 parts of sodium silicate solution to form an alkali-activated slurry.

[0012] (4) The particles obtained in step (2) are immersed in the slurry obtained in step (3), mixed evenly to completely coat the particles, and then the particles are formed into aggregate using a pelletizing machine to obtain a temperature gradient composite aggregate with a particle size of 10 to 26.5 mm.

[0013] Preferably, after the temperature gradient composite aggregate is formed, it needs to be placed in an indoor environment for 2 days, placed in 20° C. normal temperature water for curing for 10 days, and then taken out and left to dry in the air before use.

[0014] Preferably, the sintering is to pre-sinter the particles at 300-400° C. for 30-40 min, and then sinter at 700-800° C. for 100-140 min.

[0015] Preferably, the mass concentration of the sodium silicate solution is 20-30%.

[0016] Preferably, the average molecular weight of the polyethylene wax is 4000-7000.

[0017] Preferably, the particle size of the industrial waste glass powder is 5 to 20 μm.

[0018] Preferably, the aluminum sludge ash is obtained by calcining aluminum sludge discharged from a sewage treatment plant at a temperature of 340-360° C. for 2-3 hours and then passing through a 75 μm sieve.

[0019] Gangue has a high carbon content and a high water absorption rate. Using gangue as the core matrix material of composite aggregate can effectively solve the problem of low strength of concrete prepared directly with gangue as aggregate, while improving the economy of composite aggregate; high-temperature sintering can not only remove the carbon on the surface and inside of gangue, improve strength, but also stimulate surface activity; the silicon and aluminum active components in gangue can react with sodium silicate solution to form sodium silicate-aluminate gel, forming a dense layer on the surface of the particles, enhancing the strength and stability of the particles. Hollow glass microspheres have low density, high strength and good thermal insulation properties. They act as lightweight fillers, not only filling the porous structure of gangue, but also effectively improving the thermal insulation properties. Expanded perlite has good high temperature resistance and thermal insulation properties. As an inorganic binder, sodium silicate solution will form a silicate glass phase during the sintering process, which plays a bonding and reinforcing role; during the high-temperature sintering process, the Na in sodium silicate + The ions react with SiO2 in the expanded perlite to form silicate gel, which gradually forms a strong solid network structure at high temperature. At the same time, sodium silicate forms a strong bond with the surface of the glass beads, improving the overall strength and density of the material.

[0020] The expanded perlite in the inner layer can also serve as an adsorption carrier for the polyethylene wax phase change material in the middle buffer layer. The industrial waste glass powder has stable physical and chemical properties and low thermal conductivity. Through wrapping, it not only encapsulates the porous expanded perlite filler, but also forms a heat insulation layer to reduce thermal stress and temperature gradient. Polyethylene wax absorbs a large amount of heat at high temperatures, and stores heat through phase change, which reduces the internal temperature rise rate of the aggregate, which plays the main role of strength skeleton in concrete, and relieves the thermal stress of concrete. When encountering cooling, the stored heat can be dissipated, and a wide temperature platform is formed to reduce the temperature difference between the inside and outside of the concrete. In addition, microcracks will be left on the surface of the aggregate after high temperature. Polyethylene wax will melt at high temperature and fill cracks and pores. The rapid cooling process after water spraying will cause it to solidify rapidly. Combined with the high hydrophobicity of polyethylene wax, it plays a role in preventing moisture from penetrating and accumulating and repairing cracks to a certain extent.

[0021] The main components of calcined aluminum sludge ash are oxides such as aluminum oxide, silicon dioxide, and iron oxide. Aggregates are in contact with each other in concrete. Aluminum sludge ash is rich in aluminum oxide and other metal oxides, which synergistically add silicon carbide to concrete to improve the thermal conductivity of the outermost layer of aggregates and the surface of concrete, avoiding temperature stress concentration. At the same time, the alkali-activated slurry prepared based on aluminum sludge ash can effectively improve the strength of aggregates. After the composite aggregate is added to the concrete, the alkaline solution and incompletely hydrated slag powder on its surface come into contact with cement slurry, which can generate more high-quality CSH gel in the transition zone of the aggregate-cement slurry interface, thereby improving the compressive strength of concrete under normal working conditions and high temperature conditions.

[0022] Preferably, the psyllium husk gum is prepared by mixing psyllium husk with distilled water; the mass fraction of the psyllium husk is 2% to 3%.

[0023] Psyllium husk glue has hydrophilic colloid properties and contains more than 30% insoluble fiber. When added to concrete, the insoluble fiber can be distributed in large quantities and decomposed at high temperatures to form a micro-pore ventilation network structure in the concrete, which helps to release high-temperature temperature stress and high-pressure steam. There is shrinkage space during rapid cooling, which reduces the thermal stress caused by large temperature gradients and improves the crack resistance of concrete. By utilizing its thickening, water absorption and gel hydrophilic colloid properties, a mesh gel filling can be formed in the concrete to reduce pores. At the same time, its high water retention capacity can reduce the evaporation of water in the concrete, play an internal curing effect, and comprehensively improve the density and strength of the concrete; the thickening property can increase the viscosity of the cement-based slurry, which helps to improve the working performance of the concrete and reduce segregation and bleeding.

[0024] Preferably, the basalt fiber has a diameter of 10-15 μm, a length of 12-18 mm, and a breaking strength of ≥3000 Mpa.

[0025] Preferably, the particle size of the silicon carbide is 10-20 μm; the SiC mass fraction of the silicon carbide is greater than 97%, and the Fe2O3 mass fraction is less than 0.05%.

[0026] Preferably, the average molecular weight of the polyethylene glycol is 800-1000.

[0027] Preferably, the cement is one of ordinary Portland cement P·O 52.5 and P·II 52.5.

[0028] Preferably, the fly ash is Class F Grade II fly ash, with a fineness of 20 to 25 μm and a water requirement ratio of 95 to 105%.

[0029] Preferably, the sand is Grade II coarse sand with a fineness modulus of 3.3-3.7 and a mud content of no more than 4%.

[0030] Basalt fiber has high strength and modulus, excellent fireproof and high temperature resistance, and has high crack resistance and toughening effect under high temperature conditions. Psyllium husk gum can improve the interfacial bonding performance between basalt fiber and cement matrix, and its polysaccharide network structure can play a role in reinforcing fiber. The large amount of insoluble fiber and fireproof toughening fiber in psyllium husk gum can form an intricate three-dimensional network structure in concrete, which plays a role in bridging, connecting and toughening, effectively reducing the formation and expansion of concrete cracks.

[0031] Silicon carbide particles can fill the internal pores and interface defects of concrete, accelerate the generation of hydrates, make the hardened slurry structure and cementing surface more compact, and improve the strength of concrete; Silicon carbide will consume SiC molecules and form SiO2 molecules after long-term oxidation at high temperature, and then after water spray cooling, SiO2 reacts with water, calcium hydroxide, and alkali activator to generate additional CSH gel, which improves the strength of concrete; The thermal conductivity of silicon carbide can reach 490 W / (m·K), and its addition to concrete can improve the thermal conductivity of the concrete surface, avoid thermal stress concentration, and improve heat exchange efficiency, and it has the advantage of low cost compared to thermal conductive materials such as graphene and steel fiber. The disadvantage of silicon carbide is that its dispersibility in concrete is relatively poor, which affects the working performance of concrete. The polyethylene glycol and round-breasted psyllium husk glue introduced in the present invention can improve the dispersibility of silicon carbide in concrete.

[0032] Polyethylene glycol has a lubricating effect, which can reduce the friction between particles inside the concrete, improve the workability and fluidity of the concrete, and synergize with psyllium husk glue to superimpose the internal curing effect, further improve the water retention effect of the concrete, reduce plastic shrinkage and drying shrinkage, and reduce the risk of cracks in the concrete.

[0033] The present invention also provides a method for preparing the high temperature resistant rapid cooling high performance concrete, comprising the following steps:

[0034] S1. Weigh each component by weight;

[0035] S2. Mix the psyllium husk glue with the temperature gradient composite aggregate, stir for 20 to 30 seconds, and let stand for 60 to 90 seconds;

[0036] S3. Then add basalt fiber, cement, fly ash, granulated blast furnace slag, sand, 2 / 3 of water reducer and 2 / 3 of water, mix for 40 to 60 seconds until uniform, and obtain slurry;

[0037] S4. Add silicon carbide, polyethylene glycol, the remaining 1 / 3 of the water reducer and 1 / 3 of the water, and stir for 90s to 120s to obtain a high-temperature resistant rapid cooling high-performance concrete slurry.

[0038] In the steps, 2 / 3 of the water reducer refers to 2 / 3 of the total amount of the water reducer, and 1 / 3 of the water reducer refers to 1 / 3 of the total amount of the water reducer; 2 / 3 of the water refers to 2 / 3 of the total amount of the water, and 1 / 3 of the water refers to 1 / 3 of the total amount of the water.

[0039] By fully mixing the psyllium husk glue with the temperature gradient composite aggregate, a gel water film can be formed on the surface of the aggregate first, which can effectively reduce the water absorption rate of the aggregate in the later concrete mixing process and improve the internal curing effect of the concrete.

[0040] Compared with the prior art, the present invention is beneficial in that:

[0041] (1) Introduce temperature gradient composite aggregates that occupy the majority of the concrete volume. The composite aggregates are prepared using a multi-layer structure design, and the thermal conductivity coefficient decreases layer by layer. When the concrete is heated by fire, the outer layer of the aggregate has thermal conductivity and high strength, and can conduct heat to avoid thermal stress concentration. The middle layer can absorb part of the heat under thermal shock and play a buffering role. The inner layer material has low thermal conductivity and high thermal insulation to slow down the internal temperature rise, and the concrete has high high temperature resistance. When the structure is sprayed with water for rapid cooling, the outer layer begins to cool rapidly while the temperature of the inner layer gradually decreases, and the temperature gradient inside and outside the concrete is greatly reduced, thereby solving the problem of cracking and strength reduction caused by temperature stress.

[0042] (2) Using coal gangue as the composite aggregate matrix material can reduce aggregate costs, be green and environmentally friendly, and solve the problem of low strength of coal gangue aggregate concrete. High-temperature sintering is used to remove carbon from coal gangue and stimulate surface activity, and cooperate with sodium silicate solution to enhance the strength and stability of aggregate. Hollow glass microspheres act as lightweight fillers, filling the porous structure of coal gangue, and cooperate with expanded perlite to improve the thermal insulation and high temperature resistance of the inner layer of aggregate. Sodium silicate and expanded perlite form a solid network structure at high temperature, and sodium silicate forms a strong bond with the surface of glass microspheres, which improves the overall strength of aggregate. Expanded perlite is also an adsorption carrier for the intermediate layer phase change material, and industrial waste glass powder is both a phase change material encapsulation filler and a thermal insulation effect. Aluminum sludge ash cooperates with silicon carbide to improve the thermal conductivity of the concrete surface and reduce thermal stress concentration. Aluminum sludge ash and alkali-activated solution form a slurry to wrap the aggregate to improve strength, while promoting the generation of more high-quality CSH gel in the transition zone of the aggregate-cement slurry interface, thereby improving the compressive strength of concrete under conventional and high-temperature conditions.

[0043] (3) The present invention introduces psyllium husk glue, basalt fiber, silicon carbide particles, and polyethylene glycol, which work synergistically with the temperature gradient composite aggregate to improve the high temperature resistance, crack resistance, and mechanical properties of concrete, and ensure the workability of concrete. In combination with the temperature gradient composite aggregate, the deterioration of the strength and durability of concrete structures caused by factors such as large temperature gradient, shrinkage cracking, and low strength under high temperature and rapid water cooling coupling conditions can be greatly weakened, so that the structure can still retain good integrity and residual mechanical properties after experiencing fire and water spraying, thereby extending the service life of the building. DETAILED DESCRIPTION

[0044] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The invention provides a high-temperature resistant rapid cooling high-performance concrete, wherein the raw materials thereof include, by weight: 240-300 parts of cement, 60-80 parts of fly ash, 60-70 parts of granulated blast furnace slag, 700-780 parts of sand, 0.8-1.3 parts of psyllium husk glue, 1.5-2.5 parts of basalt fiber, 5-8 parts of water reducer, 155-170 parts of water, 1020-1100 parts of temperature gradient composite aggregate, 8-10 parts of silicon carbide, and 0.5-1.5 parts of polyethylene glycol; wherein the preparation method of the temperature gradient composite aggregate comprises the following steps:

[0046] (1) Preparation of inner layer matrix: 65-75 parts of coal gangue, 15-20 parts of expanded perlite powder, 8-10 parts of hollow glass microspheres and 3-5 parts of sodium silicate solution were mixed evenly, allowed to stand for 16-20 hours, granulated and sintered to obtain particles with a particle size of 4.75-16.0 mm.

[0047] (2) Preparing an intermediate heat-absorbing buffer layer: mixing the particles obtained in step (1) with polyethylene wax heated to a molten state, vacuum impregnating, and then adding industrial waste glass powder. After mechanical shaking and mixing evenly, the mixture is taken out and allowed to stand and dry to obtain composite particles with a particle size of 5 to 20 mm. The weight ratio of the particles obtained in step (1), polyethylene wax, and industrial waste glass powder is 1: (0.3 to 0.4): (0.4 to 0.5).

[0048] (3) Preparation of external thermal conductive and strength coating layer: Mix 65-75 parts of aluminum sludge ash, 15-25 parts of slag powder, and 8-12 parts of sodium silicate solution and stir evenly to form an alkali-activated slurry.

[0049] (4) The particles obtained in step (2) are immersed in the slurry obtained in step (3), mixed evenly to completely coat the particles, and then the particles are formed into aggregate using a pelletizing machine to obtain a temperature gradient composite aggregate with a particle size of 10 to 26.5 mm.

[0050] In some examples, the sintering is performed by pre-sintering the particles at 300-400° C. for 30-40 min and then sintering at 700-800° C. for 100-140 min.

[0051] In some examples, the mass concentration of the sodium silicate solution may be 20-30%. In the following specific implementation, the mass concentration of the sodium silicate solution is 25%.

[0052] In some examples, the average molecular weight of the polyethylene wax may be 3000-10000. In the following specific implementation, the average molecular weight of the polyethylene wax is 6000.

[0053] The psyllium husk glue is prepared by mixing psyllium husk with distilled water; the mass fraction of the psyllium husk can be 2% to 3%. In the following specific implementation, the mass fraction of the psyllium husk is 2%.

[0054] In some examples, the average molecular weight of the polyethylene glycol can be 800-1000. In the following specific implementation, the average molecular weight of the polyethylene glycol is 900.

[0055] In some examples, the cement may be one of ordinary Portland cement P·O 52.5 and P·II 52.5. In the following specific implementation, the cement is ordinary Portland cement P·O 52.5.

[0056] In the following examples, unless otherwise specified, the particle size of the coal gangue used is 1.18 mm to 9.5 mm; the water reducer used is a polycarboxylic acid high-performance water reducer with a water reduction rate of 28%; the particle size of the industrial waste glass powder is 5 to 20 μm; the aluminum sludge ash is aluminum sludge discharged from a sewage treatment plant, which is calcined at 340 to 360°C for 2 to 3 hours and then sieved through a 75 μm sieve; the diameter of the basalt fiber is 10 to 15 μm, the length is 12 to 18 mm, and the breaking strength is ≥3000 MPa; the particle size of the silicon carbide is 10 to 20 μm; the SiC mass fraction of the silicon carbide is greater than 97%, and the Fe2O3 mass fraction is less than 0.05%; the fly ash can be F class II fly ash, with a fineness of 20-25 μm and a water requirement ratio of 95-105%; the sand is class II coarse sand, with a fineness modulus of 3.3-3.7 and a mud content of no more than 4%; after the temperature gradient composite aggregate is formed, it needs to be placed in an indoor environment for 2 days, and then placed in 20°C normal temperature water for curing for 10 days, and then taken out and left to dry in the air before use.

[0057] In the following specific embodiments and comparative examples, unless otherwise specified, the method for preparing concrete comprises the following steps:

[0058] S1. Weigh each component by weight;

[0059] S2. The round-shell psyllium husk glue was mixed with the temperature gradient composite aggregate, stirred for 20 seconds, and allowed to stand for 80 seconds;

[0060] S3. Then add basalt fiber, cement, fly ash, granulated blast furnace slag, sand, 2 / 3 of the water reducer and 2 / 3 of the water, stir for 50s until uniform to obtain a slurry;

[0061] S4. Add silicon carbide, polyethylene glycol, 1 / 3 of the water reducer and 1 / 3 of the water, and stir for 100 seconds to obtain a concrete paste.

[0062] Example 1

[0063] A high-temperature resistant rapid cooling high-performance concrete comprises the following components in parts by weight: 240 parts of cement, 70 parts of fly ash, 60 parts of granulated blast furnace slag, 780 parts of sand, 1 part of psyllium husk glue, 2 parts of basalt fiber, 6 parts of water reducer, 160 parts of water, 1040 parts of temperature gradient composite aggregate, 10 parts of silicon carbide, and 1 part of polyethylene glycol; wherein the preparation method of the temperature gradient composite aggregate is as follows:

[0064] (1) Preparation of inner layer matrix: 65 parts of coal gangue, 18 parts of expanded perlite powder, 10 parts of hollow glass microspheres and 4 parts of sodium silicate solution were mixed evenly, aged for 16 hours, and then granulated. The particles were pre-sintered at 400°C for 30 minutes and then sintered at 700°C for 120 minutes to obtain particles with a particle size of 4.75-16.0 mm.

[0065] (2) Preparing an intermediate heat-absorbing buffer layer: mixing the particles obtained in step (1) with polyethylene wax heated to a molten state, impregnating the mixture under a vacuum of 0.01 MPa, and then adding industrial waste glass powder. The mixture is mechanically shaken, taken out, and allowed to stand and dry to obtain composite particles with a particle size of 5 to 20 mm. The weight ratio of the particles obtained in step (1), polyethylene wax, and industrial waste glass powder is 1:0.3:0.5.

[0066] (3) Preparation of external thermal conductive and strength coating layer: 70 parts of aluminum sludge ash, 20 parts of slag powder and 10 parts of sodium silicate solution were mixed and stirred evenly to form an alkali-activated slurry.

[0067] (4) The particles obtained in step (2) are immersed in the slurry obtained in step (3) and mixed evenly to completely coat the particles, and then the particles are formed into aggregate using a pelletizing machine to obtain a temperature gradient composite aggregate with a particle size of 10 to 26.5 mm.

[0068] Example 2

[0069] A high-temperature resistant rapid-cooling high-performance concrete, a temperature gradient composite aggregate and a preparation method of the concrete are the same as those in Example 1. The raw materials of the concrete include, by weight: 280 parts of cement, 70 parts of fly ash, 60 parts of granulated blast furnace slag, 730 parts of sand, 1 part of psyllium husk glue, 2 parts of basalt fiber, 6 parts of water reducer, 130 parts of water, 1100 parts of temperature gradient composite aggregate, 8 parts of silicon carbide and 1 part of polyethylene glycol.

[0070] Example 3

[0071] A high-temperature resistant rapid cooling high-performance concrete comprises the following components in parts by weight: 300 parts of cement, 70 parts of fly ash, 60 parts of granulated blast furnace slag, 700 parts of sand, 1 part of psyllium husk glue, 2 parts of basalt fiber, 6 parts of water reducer, 160 parts of water, 1020 parts of temperature gradient composite aggregate, 10 parts of silicon carbide, and 1 part of polyethylene glycol; wherein the preparation method of the temperature gradient composite aggregate is as follows:

[0072] (1) Preparation of inner layer matrix: 70 parts of coal gangue, 15 parts of expanded perlite powder, 10 parts of hollow glass microspheres and 5 parts of sodium silicate solution were mixed evenly, aged for 20 hours, and then granulated. The particles were pre-sintered at 400°C for 40 minutes and then sintered at 800°C for 100 minutes to obtain particles with a particle size of 4.75-16.0 mm.

[0073] (2) Preparing an intermediate heat-absorbing buffer layer: mixing the particles obtained in step (1) with polyethylene wax heated to a molten state, vacuum impregnating under a negative pressure of 0.01 MPa, then adding industrial waste glass powder, mixing and mechanically shaking, taking out, standing and drying, to obtain composite particles with a particle size of 5 to 20 mm; the weight ratio of the particles obtained in step (1), polyethylene wax, and industrial waste glass powder is 1:0.4:0.5.

[0074] (3) Preparation of external thermal conductive and strength coating layer: 75 parts of aluminum sludge ash, 15 parts of slag powder and 10 parts of sodium silicate solution were mixed and stirred evenly to form an alkali-activated slurry.

[0075] (4) The particles obtained in step (2) are immersed in the slurry obtained in step (3) and mixed evenly to completely coat the particles, and then the particles are formed into aggregate using a pelletizing machine to obtain a temperature gradient composite aggregate with a particle size of 10 to 26.5 mm.

[0076] Comparative Example 1

[0077] A concrete, the preparation method of the comparative concrete is basically the same as that of Example 1, except that, in the raw materials of the concrete, limestone crushed stones of equal particle size and amount are used to replace the temperature gradient composite aggregate.

[0078] Comparative Example 2

[0079] A concrete, the preparation method of the comparative concrete is basically the same as that of Example 1, except that, among the raw materials of the concrete, coal gangue aggregates with equal particle sizes and equal amounts are used to replace the temperature gradient composite aggregates.

[0080] Comparative Example 3

[0081] A concrete, wherein the preparation method of the comparative example concrete is substantially the same as that of Example 1, except that the inner layer matrix in the preparation method of the temperature gradient composite aggregate is different. The inner layer matrix of the comparative example is coal gangue obtained by pre-sintering at 400° C. for 30 minutes and then sintering at 700° C. for 120 minutes, and the mass and particle size of the inner layer matrix of the comparative example are the same as the mass and particle size of the inner layer matrix particles obtained in step (1) of Example 1.

[0082] Comparative Example 4

[0083] A concrete. The preparation method of the comparative concrete is basically the same as that of Example 1, except that in the preparation method of the temperature gradient composite aggregate, step (2) is not performed, and the prepared composite particles are used to prepare concrete.

[0084] Comparative Example 5

[0085] A concrete. The preparation method of the comparative concrete is basically the same as that of Example 1, except that in the preparation method of the temperature gradient composite aggregate, step (3) and step (4) are not performed, that is, the composite particles prepared in step (2) are directly used to prepare the concrete.

[0086] Comparative Example 6

[0087] A concrete, the preparation method of the comparative concrete is basically the same as that of Example 1, except that the temperature gradient composite aggregate is different. The aggregate of this comparative example is: 65 parts of coal gangue, 18 parts of expanded perlite powder, 10 parts of hollow glass microspheres and 4 parts of sodium silicate solution are mixed evenly, and after standing and aging for 16 hours, granulation is performed, and the particles are pre-sintered at 400°C for 30 minutes, and then sintered at 700°C for 120 minutes to obtain aggregates with a particle size of 10~26.5 mm.

[0088] Comparative Example 7

[0089] A concrete, the difference between this comparative concrete and Example 1 is that no psyllium husk gum is added to the concrete, and the basalt fiber is replaced by polypropylene fiber, and the preparation method is as follows:

[0090] S1. Weigh each component by weight;

[0091] S2. The temperature gradient composite aggregate, polypropylene fiber, cement, fly ash, granulated blast furnace slag, sand, 2 / 3 of the water reducer and 2 / 3 of the water were stirred for 50 seconds until a uniform state to obtain a slurry;

[0092] S3. Add silicon carbide, polyethylene glycol, 1 / 3 of a water reducer and 1 / 3 of water and stir for 100 seconds to obtain a concrete paste.

[0093] Comparative Example 8

[0094] A concrete, the difference between this comparative example concrete and Example 1 is that silicon carbide is not added to the concrete, and the preparation method is as follows:

[0095] S1. Weigh each component by weight;

[0096] S2. The round-shell psyllium husk glue was mixed with the temperature gradient composite aggregate, stirred for 20 seconds, and allowed to stand for 80 seconds;

[0097] S3. Then add basalt fiber, cement, fly ash, granulated blast furnace slag, sand, 2 / 3 of the water reducer and 2 / 3 of the water, stir for 50s until uniform to obtain a slurry;

[0098] S4. Add polyethylene glycol, 1 / 3 of the water reducing agent and 1 / 3 of the water, and stir for 100 seconds to obtain a concrete paste.

[0099] Comparative Example 9

[0100] A concrete. The preparation method of the comparative concrete is basically the same as that of Example 1, except that in the preparation method of the temperature gradient composite aggregate, the hollow glass microspheres in step (1) are replaced by an equal number of expanded perlite powder.

[0101] High temperature rapid cooling condition test method:

[0102] (1) Composite aggregate performance test: 6-8 kg of dry composite aggregate was taken for performance index test before and after working condition; concrete specimen test: the side length was 150 mm × 150 mm × 150 mm, and it was cured under standard conditions for 28 days. When it reached the curing age, it was dried (placed in an environment with a temperature of 105℃±5℃ for 48 hours);

[0103] (2) Place the dried specimen in a high temperature furnace for high temperature testing. After the high temperature furnace reaches 500±10℃, keep the temperature constant for 1 hour. Take out the specimen and immediately spray water to cool it down. The water spray cooling process refers to GB 50974-2014 "Technical Specifications for Fire Water Supply and Fire Hydrant Systems" and controls the water spray flow rate to 15 L / s. The four-sided circulation water spraying lasts for 30±2 minutes.

[0104] Referring to GB / T 14685-2022 "Pebbles and Crushed Stones for Construction", the crushing values ​​of the composite aggregates prepared in Example 1, Example 3, Comparative Examples 3 to 5, and Comparative Example 8, the limestone crushed stone of Comparative Example 1, and the coal gangue aggregate of Comparative Example 2 were tested before and after the high-temperature rapid cooling condition; from each of the above examples, 10 aggregates with larger particle sizes were randomly selected to observe the changing characteristics of the surface cracks of the aggregates after the condition, and to make a qualitative judgment on the cracks. The number of cracks is divided into 4 levels: few, medium, more, and more, and the overall coarseness of the cracks is divided into 3 levels: fine, coarse, and coarse. The test results are shown in Table 1.

[0105] Table 1: Aggregate performance test results

[0106]

[0107] From the test results in Table 1, it can be seen that the temperature gradient composite aggregate used in Example 1 and Example 3 has a crushing value before the working condition is slightly smaller than the conventional limestone aggregate in Comparative Example 1, and is significantly smaller than the coal gangue aggregate in Comparative Example 2; after the working condition, the crushing values ​​of the composite aggregates in Example 1 and Example 3 are both less than 20%, and the increase in the crushing value is less than 90%. The aggregates after the working condition can still meet the use requirements of Class II crushed stone, and the apparent cracks are generally few and fine, and the anti-cracking effect after the high-temperature rapid cooling working condition is obvious. The crushing value of the limestone aggregate in Example 1 after the working condition increased by 153%, and the apparent cracks were more and coarser, and the overall anti-cracking performance of the aggregate under the working condition was poor; the crushing value of the untreated coal gangue aggregate in Example 2 after the working condition increased by 127.1%, and the apparent cracks were more and coarser. This is because the carbon in the coal gangue can be removed and the strength of the coal gangue can be improved under high temperature conditions, but because it has more apparent pores, under high temperature rapid cooling conditions, due to the large surface temperature stress, its surface cracks accelerate deterioration. The test results of comparative examples 3 to 6 show that each layer of the temperature gradient composite aggregate is helpful for the overall realization of the temperature stress of the aggregate under the weakening condition, and none of them can be missing, and the materials used in each layer can achieve the purpose of the corresponding functional effect; the crushing value of comparative example 9 after the working condition is 21.8%, the crushing value increase is 101.85%, and the apparent cracks are medium and coarse, which shows that the hollow glass microspheres in the embodiment act as a lightweight filler, which can fill the porous structure of coal gangue and synergistically expand perlite, which can effectively improve the thermal insulation and high temperature resistance of the inner layer of the aggregate.

[0108] The mechanical properties of concrete were tested according to GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Ordinary Concrete"; the anti-permeability of concrete was tested according to GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The "seepage height method" was used to determine the average seepage height of concrete under constant water pressure, which is expressed as the concrete anti-water penetration performance. The larger the average seepage height of the specimen, the worse the anti-water penetration performance of the specimen. In terms of concrete crack resistance, considering that the concrete cube specimen was used in this test, the early crack resistance test method in GB / T 50082-2009 was referred to, and the apparent cracks on the six faces of the cube were observed and qualitatively evaluated. The number of cracks was divided into four levels: few, medium, more, and more, and the overall coarseness of the cracks was divided into three levels: fine, coarse, and coarse. At the same time, a 50x electronic magnifying glass was used to measure the maximum crack width. The test results are shown in Table 2.

[0109] Table 2: Concrete performance test results of Examples 1 to 3 and Comparative Examples 1 to 9

[0110]

[0111] It can be seen from the test results in Table 2 that in terms of compressive strength, as the amount of adhesive increases, the design grade of the concrete mix ratio of Examples 1 to 3 is improved, the compressive strength is improved and all are higher than half the design grade, and the mechanical properties are excellent. In addition, during the mixing process, it was found that the slump of the embodiments can reach more than 200mm, the cohesiveness and water retention are also good, and it has good construction pumpability. After the high-temperature rapid cooling working condition, the residual strength values ​​of the concrete of Examples 1 to 3 are all above 85%. In terms of water seepage height, the water seepage height increase values ​​before and after the working condition are basically below 50%, and a certain density and impermeability can still be maintained after high-temperature rapid cooling. In terms of crack resistance, after the working condition, the apparent cracks of Examples 1 to 3 are all small and fine, with a maximum crack width of 0.26mm.

[0112] From the test results of comparative examples 1-2, the performance of the concrete using temperature gradient composite aggregate in Example 1 is better than that of the concrete using conventional limestone aggregate, and is significantly better than that of the concrete using coal gangue aggregate; after high temperature rapid cooling, the residual strength values ​​of the concrete in comparative examples 1-2 are only 74.8% and 70.2% respectively; the water seepage height increase value is about 44 percentage points and 47 percentage points higher than that in Example 1, and the surface cracks are more and coarser. This is mainly because limestone aggregate and coal gangue aggregate do not have heat transfer, heat absorption and heat insulation properties, and their thermal expansion coefficients are close to those of cement-based materials, while coal gangue aggregate itself has many defects and low strength. Under the working conditions, the concrete surface and interior prepared by the two aggregates have large temperature stresses, the interface between the hydration product and the aggregate is destroyed and the bonding strength is reduced, and its compactness and crack resistance performance deteriorate more significantly.

[0113] The aggregates used in Comparative Examples 3 to 6 are different from the temperature gradient composite aggregates in Example 1 in that the inner layer has no heat insulation design, no intermediate heat absorption buffer layer, and no external heat conduction and strength wrapping layer. The compressive strength of Comparative Example 6 is the lowest, which is 40.2MPa. The residual values ​​of compressive strength after the working condition are 80.2%, 81.4%, 76.1% and 77.4%, respectively, which are significantly lower than those in Example 1. The water seepage height increase value is 13 percentage points, 18 percentage points, 26 percentage points and 28 percentage points higher than that in Example 1, respectively, and the anti-permeability performance decreases significantly. At the same time, the maximum crack width after the working condition also increases to varying degrees. This shows that the temperature gradient composite aggregates with multi-layer structure design, each layer helps to reduce the performance of concrete under high temperature and rapid cooling conditions; the outer layer has high thermal conductivity and strength, which can conduct heat to avoid thermal stress concentration, the middle layer can absorb part of the heat under thermal shock, and play a buffering role. The inner layer material has high thermal insulation, which slows down the internal temperature rise. Under high temperature and rapid cooling conditions, the internal and external temperature gradients of concrete can be greatly reduced, and the cracking and strength reduction conditions are weakened. In addition, the temperature gradient composite aggregate in Comparative Example 4 does not contain polyethylene wax, and its water permeability resistance before and after working conditions is significantly lower than that of the comparative example. This demonstrates that polyethylene wax can melt at high temperatures to fill cracks and pores, and the rapid cooling process after water spraying will solidify it. Combined with the high hydrophobicity of polyethylene wax, it can prevent moisture infiltration and accumulation in concrete and repair cracks to a certain extent.

[0114] From the test results of proportions 7 to 9, the residual strength values ​​are 77.7%, 80.7%, and 80.1%, respectively, and the maximum crack widths are 0.42 mm, 0.35 mm, and 0.30 mm, respectively, and the performance is significantly weaker than that of Example 1. This shows that the synergistic effect of basalt fiber and insoluble fiber in psyllium husk glue has a significant improvement effect on the strength of concrete before and after working conditions compared with conventional polypropylene fiber. At the same time, the excellent fire resistance and high temperature resistance of basalt fiber, the reinforcement, bridging, connection and toughening effect of psyllium husk glue on fiber can significantly improve the crack resistance of concrete under high temperature rapid cooling; silicon carbide can fill the internal pores and interface defects of concrete, accelerate the formation of hydrates, and generate additional CSH gel at high temperature to improve the strength of concrete. At the same time, its addition to concrete can increase the thermal conductivity of the concrete surface, avoid thermal stress concentration, improve heat exchange efficiency, and help reduce the surface temperature stress of concrete under high temperature rapid cooling conditions; hollow glass microspheres can effectively insulate, fill and improve the overall strength and density of aggregates, and have an effect on the concrete's resistance to degradation under high temperature rapid cooling conditions.

[0115] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high temperature resistant rapid cooling high performance concrete, characterized in that: The raw materials of the concrete include, by weight: 240-300 parts of cement, 60-80 parts of fly ash, 60-70 parts of granulated blast furnace slag, 700-780 parts of sand, 0.8-1.3 parts of psyllium husk glue, 1.5-2.5 parts of basalt fiber, 5-8 parts of water reducer, 155-170 parts of water, 1020-1100 parts of temperature gradient composite aggregate, 8-10 parts of silicon carbide, and 0.5-1.5 parts of polyethylene glycol; wherein the preparation method of the temperature gradient composite aggregate includes the following steps: (1) Preparation of inner layer matrix: 65-75 parts of coal gangue, 15-20 parts of expanded perlite powder, 8-10 parts of hollow glass microspheres and 3-5 parts of sodium silicate solution are mixed evenly, and after standing and aging, granulation and sintering are performed to obtain particles with a particle size of 4.75-16.0 mm; (2) Preparing an intermediate heat-absorbing buffer layer: mixing the particles obtained in step (1) with polyethylene wax heated to a molten state, vacuum impregnating, then adding industrial waste glass powder, mechanically shaking and mixing, taking out, standing and drying, to obtain composite particles with a particle size of 5 to 20 mm; (3) Preparation of external thermal conductive and strength coating layer: 65-75 parts of aluminum sludge ash, 15-25 parts of slag powder, and 8-12 parts of sodium silicate solution are mixed evenly to form an alkali-activated slurry; (4) immersing the particles obtained in step (2) into the slurry obtained in step (3), mixing them evenly to completely coat the particles, and then forming the aggregate to obtain a temperature gradient composite aggregate with a particle size of 10 to 26.5 mm; The aluminum sludge ash is obtained by calcining aluminum sludge at 340-360°C for 2-3h and then sieving it; The psyllium husk glue is prepared by mixing psyllium husk and water.

2. The high temperature resistant rapid cooling high performance concrete according to claim 1, characterized in that: In step (1), the sintering is to pre-sinter the particles at 300-400°C for 30-40 minutes and then sinter at 700-800°C for 100-140 minutes.

3. The high temperature resistant rapid cooling high performance concrete according to claim 1, characterized in that: In step (2), the weight ratio of the particles obtained in step (1), polyethylene wax, and industrial waste glass powder is 1: (0.3-0.4): (0.4-0.5).

4. The high temperature resistant rapid cooling high performance concrete according to claim 1, characterized in that: In step (2), the average molecular weight of the polyethylene wax is 4000-7000.

5. The high temperature resistant rapid cooling high performance concrete according to claim 1, characterized in that: In steps (1) and (3), the mass concentration of the sodium silicate solution is 20-30%.

6. The high temperature resistant rapid cooling high performance concrete according to claim 1, characterized in that: The basalt fiber has a diameter of 10-15 μm, a length of 12-18 mm, and a breaking strength of ≥3000 Mpa.

7. The high temperature resistant rapid cooling high performance concrete according to claim 1, characterized in that: The average molecular weight of the polyethylene glycol is 800-1000.

8. The method for preparing high temperature resistant rapid cooling high performance concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Weigh each component by weight; S2. Mix the psyllium husk glue with the temperature gradient composite aggregate, stir for 20 to 30 seconds, and let stand for 60 to 90 seconds; S3. Then add basalt fiber, cement, fly ash, granulated blast furnace slag, sand, 2 / 3 of water reducer and 2 / 3 of water, mix for 40 to 60 seconds until uniform, and obtain slurry; S4. Add silicon carbide, polyethylene glycol, the remaining 1 / 3 of the water reducer and 1 / 3 of the water, and stir for 90s to 120s to obtain a high-temperature resistant rapid cooling high-performance concrete slurry.

Citation Information

Patent Citations

  • High-temperature-resistant concrete and preparation method thereof

    CN115124291A

  • Porous reticular aggregate / carbon fiber composite modified high-temperature-resistant and high-strength concrete

    CN117819909A

  • High-temperature-resistant concrete and preparation method thereof

    CN117886568A

  • Ceramsite sand produced by using coal gangue and processing technology of ceramsite sand

    CN109942275A